Optimization and accuracy analysis in pose measurement of the subreflectors of large antennas based on stereo structured light - Zhang, Xuan; Lin, Shangmin; Wang, Hu; Gao, Ming; Jin, Yu; Lai, Yunqiang; Lv, Hong (Frontiers in Physics, 2024)
Accuracy of the pointing error in subreflector is of great importance to the large steerable radio telescope, so that the measurement of six degree-of-freedom (DOF) poses of the subreflector is crucial, which is measured by the detector and the laser array. The errors in pose measurement system of the subreflector contain random measure errors and fitting iteration errors, all of them will add up to the pose measurement which affects the accuracy of the 6-DOF parameters. This paper proposed the accuracy analysis method in pose measurement of the subreflector of large antennas, which include the error in variable (EIV) model in laser three-dimensional points space linear fitting, iterative accuracy analysis of spatial equations in Newton's downhill method and the analysis of the adjustment theory of the Bursa model. The experimental results show that the measure time in 6-DOF pose of the subreflector in large-aperture antenna is at most 0.5s while the measurement accuracy error of translation is within 0.0131mm and the error of rotation is within 0.2323°, which indicates that pose measurement method of the subreflector of large antennas based on stereo structured light is efficient and applicable enough to analysis the measurement system accuracy.